Study on Electricity Utilization Rules of Light Sockets in Governmental Office Buildings in Chongqing - Yong Ding; Donglin Zhang; Baizhan Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper is based on the energy consumption monitoring platform of the office buildings and large-sized public buildings of the state organs in Chongqing. The writer selected one office building with complete set of data and normal operation as the case building to analyze electricity for lighting sockets in the building and find out the rule and features of electricity utilization. In addition, we selected 5 buildings to demonstrate the rule and compared the results with the standard plants. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4457